Parametric identification of damaged dynamic systems with hysteresis and slip - Ceravolo, Rosario; Zanotti Fragonara, Luca; Erlicher, S.; Bursi, O. S. (IOP Publishing, 2011)
The improvement of performance-based seismic design techniques requires the understanding of the overall behaviour of a structure up to collapse. Therefore, both experimental data and analytical models are needed. In a greater detail, material and geometrical nonlinearities, strength degradation and stiffness deterioration should be identified. Also in view of probabilistic-based simulations, hysteretic models, i.e. models able to describe with accuracy the hysteretic and degrading nature of the dynamic response of structures, have to be striven for. At higher level of excitation or under seismic loading, civil structures can exhibit slip effects. This paper presents a technique for the identification of non-linear in framed systems. A new a model for simulating slip effects is also introduced, which demonstrated to be suitable for identification purposes.